Endothelial bioreactor system ameliorates multiple organ dysfunction in septic rats - Ma, Shuai (Intensive Care Med Exp, 2016)
BACKGROUND: The endothelium is a potentially valuable target for sepsis therapy. We have previously studied an extracorporeal endothelial cell therapy system, called the endothelial bioreactor (EBR), which prolonged the survival time of endotoxemia sepsis in swine. To further study of the therapeutic effects and possible mechanisms, we established a miniature EBR system for septic rats induced by cecal ligation and puncture (CLP). METHODS: In the miniature EBR system, the extracorporeal circulation first passed through a mini-hemofilter, and the ultrafiltrate (UF) was separated, then the UF passed through an EBR (a 1-mL cartridge containing approximately 2 × 10(6) endothelial cells grown on microcarriers) and interact with endothelial cells. Eighteen hours after CLP, the rats were treated for 4 h with this extracorporeal system containing either endothelial cells (EBR group) or no cells (sham EBR group). Physiologic and biochemical parameters, cytokines, endothelial functions, and 7-day survival time were monitored. In vitro, the pulmonary endothelial cells of the septic rats were treated with the EBR system and the resulting changes in their functions were monitored. RESULTS: The EBR system ameliorated CLP-induced sepsis compared with the sham EBR system. After CLP, the 7-day survival rate of sham-treated rats was only 25.0 %, while in the EBR-treated group, it increased to 57.1 % (p = 0.04). The EBR system protected the liver and renal function and ameliorated the kidney and lung injury. Meanwhile, this therapy reduced pulmonary vascular leakage and alleviated the infiltration of inflammatory cells in the lungs, especially neutrophils. Furthermore, after the EBR treatment both in vivo and in vitro, the expression of intercellular adhesion molecule-1 and the secretion of CXCL1 and CXCL2 of pulmonary endothelium decreased, which helped to alleviate the adhesion and chemotaxis of neutrophils. In addition, the EBR system decreased CD11b expression and intracellular free calcium level of peripheral blood neutrophils, modulated the activation of these neutrophils. CONCLUSIONS: The EBR system significantly ameliorated CLP-induced sepsis and improved survival and organ functions. Compared with the sham EBR system, this extracorporeal endothelial therapy may be involved in modulating the function of pulmonary endothelial cells, reducing the adhesion and chemotaxis of neutrophil, and modulating the activation of peripheral blood neutrophils. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s40635-016-0097-y) contains supplementary material, which is available to authorized users.